Pattern of antibiotic prophylaxis practice for dental procedures in children with congenital heart disease - Jama'iah Mohd Sharif; Raja Zarina Raja Shahardin; Ganasalingam Sockalingam (Wolters Kluwer Medknow Publications, 2020)
Background: Various antibiotic prophylaxis guidelines have been published such as the American Heart Association 2007, British Society for Antimicrobial Chemotherapy 2006, National Institute for Health and Clinical Excellence 2008, European Society of Cardiology 2015, and in Malaysia, the National Antibiotic Guideline 2014 and Clinical Practice Guidelines for the Prevention, Diagnosis and Management of Infective Endocarditis 2017. The aim of the study is to determine the pattern of antibiotic prophylaxis practice for dental procedure in children with congenital heart disease (CHD) at the Department of Paediatric Dentistry, Kuala Lumpur Hospital. Materials and Methods: A comparative cross-sectional study of dental records from 2010 to 2015 was done by collecting data on the source and reason of referral, types of heart condition, dental procedure, and antibiotic given. Results: There were 210 patients; 69.5% had acyanotic CHD, 21.9% cyanotic CHD, 6.7% repaired CHD with residual defects, and 1.9% with previous infective endocarditis. Slightly more than 58% were referred from government doctors (pediatric cardiologist and National Heart Institute). The common cause for referral was dental assessment (47.6%). Antibiotics were prescribed to 23.3% (49/210) patients, of which, 34.7% was given ampicillin or amoxicillin/clavulanic acid. About 96% of cyanotic heart cases undergoing invasive dental procedures were prescribed antibiotic prophylaxis. Almost 31% were prescribed with antibiotic prophylaxis even though it was not indicated. Conclusion: This study shows that there is variability in prescribing antibiotic prophylaxis, and it is important for dental clinicians to standardize the practice of giving antibiotic prophylaxis.